The effect of pollen grain morphology on sugars content of bee-collected pollen: the significance of size and exine ornamentation. Issue 5 (2nd September 2020) - Dimou, Maria; Liolios, Vasilios; Rodopoulou, Maria-Anna; Tananaki, Chrysoula
Abstract: Sugars constitute the main component of bee-collected pollen, which may vary significantly among different pollen taxa according to their botanical origin and the surrounding vegetation. In this study, we investigated the significance of the pollen grain volume and exine sculpture on the sugars content of bee-collected pollen. We analysed the sugar content of 30 monofloral pollen pellets using high-performance liquid chromatography and we measured the volume of the pollen grains. The content of total sugars of pollen pellets was on average 421.0 g kg −1 .We found that the volume of pollen grain affects the total content of sugars in bee-collected pollen in a statistically significant way and smaller size pollen grains had comparatively higher sugar values. On the contrary, we found no clear evidence regarding the significance of the exine ornamentation on sugar content. The results revealed that the presence of sugars in bee-collected pollen is a multifactorial issue as several parameters such as the volume of pollen grains, the botanical origin, the flowering season and surrounding vegetation may influence the results.